Sosialisasi Kebijakan Penanggulangan Penggunaan Alat Tangkap Yang Tidak Ramah Lingkungan Di Bidang Perikanan - Hehanussa, Deassy Jacomina Anthoneta; Lewerissa, Yanti Amelia; Tuhumury, Carolina (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: The use of fishing gear that is not environmentally friendly in fishing activities is often carried out by people around the Seram Sea, especially fishermen in West Seram Regency. This shows the lack of public understanding of the negative impacts caused by destructive fishing activities. Even though there are various regulations governing capture fisheries activities that are not environmentally friendly.Purposes of Devotion: Community service carried out through outreach activities to the Kairatu Village community regarding the Socialization of Policies for Handling Unenvironmentally Friendly Fishing Gear in the Fisheries Sector. Method of Devotion: The method used in the First Stage: we carried out initial data collection to determine the needs of the Kairatu Village community. Second stage: we process the initial data and then present it through outreach activities. Third Stage: we provide outreach to both village officials and the community who attend. Fourth Stage: we carried out final data collection to evaluate the socialization we carried out.Results of the Devotion: As a result, the community understands the impact of using fishing gear that is not environmentally friendly in the fisheries sector as well as the legal consequences that arise if the community continues to carry out destructive fishing activities using fishing gear that is not environmentally friendly.